Higher Education: literacy in discursive genres - Lina Calle Arango (Universidade Federal do Rio Grande do Sul, 2018)
From higher education, academic literacy means to familiarize students with the discourse genre of the profession. Therefore, the aim of this text is to reflect on an alternative way to teach discursive genres in academic literacy in higher education environments, having in mind that the students must constantly develop the communicative and pragmatic skills of their professional field. In this, it is essential to familiarize them with situations that have regularities of the scope itself, although loaded with contextual and referential details. But this process will be incomplete if it is not accompanied by a later reflection.